2015
DOI: 10.1111/cpf.12255
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase Glu298Asp gene polymorphism influences body composition and biochemical parameters but not the nitric oxide response to eccentric resistance exercise in elderly obese women

Abstract: Both endothelial nitric oxide synthase (eNOS) gene polymorphism and nitric oxide (NO) are involved in important cardiovascular, muscular and inflammatory physiological mechanisms during ageing and response to exercise. The aim of this study was to investigate the NO kinetic response following an acute eccentric resistance exercise (ERE) session and the possible effect of the Glu298Asp eNOS gene polymorphism in elderly obese women. Eighty-seven women (age 69·4 ± 6·1 years, body weight 74·9 ± 12·7 kg, height 151… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(40 reference statements)
0
5
0
2
Order By: Relevance
“…We certainly agree that our definition of responsiveness was specific to our study population and exercise type (ERE). Limitations in this study such as genetic variation, the use of one exercise as compared with seven exercises in another study [19], absence of a non-obese group and the lack of a specific diet control as the timing and composition of dietary intake can modulate training responses [28]. In addition, we do not know if the exercise stimulus would have been low enough in the small group of LR to induce a CK and NO release.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We certainly agree that our definition of responsiveness was specific to our study population and exercise type (ERE). Limitations in this study such as genetic variation, the use of one exercise as compared with seven exercises in another study [19], absence of a non-obese group and the lack of a specific diet control as the timing and composition of dietary intake can modulate training responses [28]. In addition, we do not know if the exercise stimulus would have been low enough in the small group of LR to induce a CK and NO release.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the CK reference values for women are 40 to 150 U/l [14). Although the magnitude of CK activity after exercise was small, when accompanied with NO increments after exercise in the HR subjects, it could be indicative of muscle damage and regeneration [28]. The greater NO response following an ERE session and the greater CK response in the HR subjects might infer a better adaptive response to injury and regeneration in these individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Além disso, Tajra et al, (2014) também observaram em idosas obesas, aumento na CK e IL-6 após 48hrs e 24hrs após sessão de TFE, porém tais níveis foram considerados normais e não indicativos de excesso de dano muscular assim como no presente estudo. E estudo de Teixeira et al, (2015), indicando que o protocolo de TFE utilizado é suficiente para induzir dano muscular pela mediado através da CK, mas sem uma resposta exacerbada.…”
Section: Resultsunclassified
“…Por fim, foram selecionados apenas 3 artigos que se encaixavam nos critérios de inclusão. Destes, apenas um tratava sobre a respostas do polimorfismo do gene em eNOS ao exercício excêntrico em idosas (TEIXEIRA et al, 2015), dois sobre treinamento resisto e as influências do polimorfismo genético de ECA (MOTA et al, 2013;PEREIRA et al, 2013), e nenhum trazia informações sobre polimorfismos de APOE e treinamento.…”
Section: Fundamentação Teóricaunclassified
“…We revealed no associations for G894T or C774T SNPs with biochemical parameters of lipid and carbohydrate metabolism in MetS patients with or without SCH. However, some other studies demonstrated the associations between G894T SNP and plasma triglycerides in Caucasian patients with obesity and T2DM [ 49 , 50 ]. Moreover, NOS3 G894T polymorphism is likely a predictor for persistent hyperglycemia for individuals who have a compromised glucose tolerance and atherogenic lipid profile in Asian populations [ 30 , 46 , 51 ].…”
Section: Discussionmentioning
confidence: 99%